1 - Diagnostic du système éducatif béninois Eléments pour une réforme novatrice des systèmes éducatifs africains: by Dénis Amoussou-Yeye - Dénis Amoussou-Yeye, (Africa Development, 1996)
This article shows that in Benin, the School Guidance Law of 23 June 1995 has shortened the educational system cycles, reduced the operational costs, professionalised higher education and introduced national languages in the curricula However, the States Generals of 9 October 1990, have concluded that the Béninois educational system vmgb blocked following an evaluation of its internal and external efficiency. The author suggests self-finding for graduate and post-graduate studies and refocussed educational and pedagogical strategies.